Halls at Borre: the discovery of three large buildings at a Late Iron and Viking Age royal burial site in Norway. (February 2020) - Tonning, Christer; Schneidhofer, Petra; Nau, Erich; Gansum, Terje; Lia, Vibeke; Gustavsen, Lars; Filzwieser, Roland; Wallner, Mario; Kristiansen, Monica; Neubauer, Wolfgang; Paasche, Knut; Trinks, Immo
Abstract: Abstract : Borre in Norway is famous for its Late Nordic Iron and Viking Age (AD 400–1050) monumental burial mounds. Recently, ground-penetrating radar (GPR) surveys have revealed three large structures close to the mound cemetery. Their unusual layout and size, and location within such a prominent burial site, suggest that they were halls—high-status buildings mentioned in the Nordic sagas. The authors present the GPR results, discuss the buildings' typological classification and provide a preliminary chronological framework. The latter suggests that the buildings coexisted with some of the burial mounds, and raises important questions about the significance of such buildings in Nordic mound-building societies.